European symposium on the awareness of allergy: report of the promotional campaign in the European Parliament (26–28 April 2016). Issue 2 (6th January 2017) - Muraro, A.; Steelant, B.; Pietikainen, S.; Borrelli, D.; Childers, N.; Callebaut, I.; Kortekaas Krohn, I.; Martens, K.; Pugin, B.; Popescu, F.‐D.; Vieru, M.; Jutel, M.; et al.
Abstract: From 26 to 28 of April 2016, an allergy awareness campaign was organized by the European Academy of Allergy and Clinical Immunology and the European Federation of Allergy and Airway Diseases Patients Associations in the European Parliament in Brussels, with support of the European Parliament's Interest group on Allergy and Asthma and was co‐hosted by the Members of the European Parliament David Borrelli, Sirpa Pietikainen and Nessa Childers. Skin prick tests (SPTs) were performed to gain attention for the increasing prevalence of allergic airway diseases in Europe. Since more than 30% of the total European population suffers from airway allergies and asthma, reaching a higher level of awareness and elaboration of an active prevention plan is mandatory. Of the 406 individuals undergoing SPT in the European Parliament, 211 participants (52%) reported to have suffered from an allergy in the past, with allergic symptoms being present in the nose and eyes (40% and 36%, respectively), the skin (27%), lower airways (14%) and the gut (8%). Of the 381 SPT with reliable results, cutaneous hypersensitivity was found in 201 (53%) participants. Of those with positive SPT ( n  = 201), 70 participants (35%) were monosensitized while 131 participants (65%) were polysensitized. The positive skin reactions were found mostly for grass pollen ( n  = 108), followed by Dermatophagoides pteronyssinus ( n  = 105), Dermatophagoides farina ( n  = 96) and birch pollen ( n  = 85). Of note, 54 individuals (14% of the total tested population) without reported allergy or allergic symptoms showed a positive SPT without clinical relevance. This report summarizes the main idea and goals of the symposium: chronic airway diseases are a major and growing health problem in Europe. Therefore, a joint preventive action plan needs to be developed for a better health status of European citizens.